Planning for Regional Food Equity. Issue 3 (3rd July 2021) - Mui, Yeeli; Khojasteh, Maryam; Judelsohn, Alexandra; Sirwatka, Avery; Kelly, Sylvia; Gooch, Patrick; Raja, Samina
Abstract: Problem, research strategy, and findings: Scholars in planning and public health have increasingly called attention to inequities in the food system. To evaluate and address these challenges, local and regional governments have developed and implemented a variety of plans over the last 2 decades. The role of regional food planning, however, remains understudied. Most assessments of plans, vis-à-vis food systems, fall short in gauging how plans address structural problems that lead to poor access to food. We used 130 indicators to conduct a comparative plan evaluation of adopted regional plans ( n = 47) that address key dimensions of food equity in the United States from 2008 to 2018. Specifically, we quantitatively and qualitatively investigate how these plans address the nutritional adequacy of food; affordability and cultural preferences of food for all people; and social equity, spatial equity, and people's agency in the food system. Findings show regional plans have a relative lack of attention to the affordability of food and social equity in the food system. Across different types of plans, sustainability plans focused on food equity to the greatest extent. Within plans, language about food equity was lacking in particular sections, namely in the vision, goals, and objectives; in the factual basis of plans; and in sections pertaining to monitoring progress toward food equity. Takeaway for practice: We uncover opportunities for planners to promote food equity through strategies such as improving affordability of healthy food; supporting social equity and people's agency in the food system through improved governance; incorporating food equity into the vision, goals, and objectives of regional plans; leveraging different types of plans to advance food equity; strengthening empirical evidence on varied dimensions of food equity; and improving the monitoring of proposed actions and outcomes.